Life in a country album - Handal, Nathalie, 1969- (Pitt poetry series., 2019)
From migrations to pop culture, loss to la derive, Life in a Country Album is a soundtrack of the global cultural landscape--borders and citizenship, hybrid identities and home, freedom and pleasure. It's a vast and moving look at the world, at what home means, and the ways we coexist in an increasingly divided world. These poems are about the dialects of the heart--those we are incapable of parting from, and those that are largely forgotten. Life in a Country Album is a vital book for our times. With this beautiful, epic collection, Nathalie Handal affirms herself as one of our most diverse and important contemporary poets.